Efecto del Liderazgo sobre el Bienestar Subjetivo del Emprendedor - VARGAS-MORÚA, Gioconda (Journal Of Exact Sciences and Technological Applications, 2021)
Leadership´s effect on entrepreneur´s subjective well-being is positive. If it is also mediated by the satisfaction of basic psychological needs (autonomy, competence and relationships), the effect increases. The entrepreneur who has the ability to make decisions, interact and direct their projects, also meets their needs and therefore, experiences a greater sense of well-being.